UPAYA MENINGKATKAN PROFESIONALISME KARYAWAN BANQUET DI F&B DEPARTMENT PRIME PARK HOTEL PEKANBARU - Windi Wiliana; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Currently, the business in the hospitality sector is growing rapidly. This is due to the development of the city and the mobility of the population. In addition, it is also due to the tourism factor which brings in many visitors or tourists who come to visit a tourist attraction in an area. One of the hoteliers at Pekanbaru Prime Park Hotel Pekanbaru which is a 4-star hotel located in the business center and the Pekanbaru Tour & Travel Government which is still running well amid the covid-19 pandemic. Prime Park Hotel Pekanbaru is an ideal place for guests on business trips and tourists to rest with family, friends and so on. In SeptemberNovember 2021, it has increased from month to month. However, due to the small number of employees, the work is not conducive, because from here the management uses a lot of casual children, so for work there are many miss communication between the staff and casual parties. With the implementation of discipline from each employee, and increasing professionalism for each employee, This will make every task and responsibility of the job easier to carry out. Therefore, this study aims to determine how the role of the Banquet Supervisor increases the professionalism of employees at the F&B Department of Prime Park Hotel Pekanbaru. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. And in carrying out the role as Supervisor, the supervisor carries out the Interpersonal Role or the Strategic Interpersonal Role, Information Role and Decisional Role. Based on the results of the research that has been done, for the overall results of observations and interviews, it can be concluded that the role of the Banquet Supervisor increases the professionalism of employees at the F&B Department of Prime Park Hotel Pekanbaru. has been fully running even though there are still shortcomings. Keywords: Efforts, Banquet, Profesionalisme